Giải số bài toán ô nhiễm khí bằng phương pháp luân hướng - Điều, Nguyễn Công (Journal of Computer Science and Cybernetics, 2016)
In this paper  a version of the alternating direction method for solution of multidimensional problems is considered. We show that under some conditions, this method can be applied to the air pollution problem. Numerical results of the three – dimensional air pollution model with a point source are presented and compaired with results of the local one – dimensional method and the splitting method.